Student Science Literacy At SMA Negeri 1 Kambera - Marleni , Rosalia Ndapa Huda; Remindima, Ndawa Lu Remindima (Journal of Education Technology and Inovation, 2025)
This study aims to measure the level of science literacy skills among students of SMA Negeri 1 Kambera. Science literacy is the ability to understand, use, and apply science knowledge to explain natural phenomena and make informed decisions based on concrete evidence. This ability is crucial to assist students in their science development. This study used a descriptive quantitative-quantitative (mixed method) method with data collection through literacy tests, interviews, and observations. A total of 70 students participated in the testing process, and interviews were conducted with three biology teachers. The results showed that the average science literacy skills of students were in the high category, namely 80.3%. The first indicator scored 78%, the second indicator scored 91%, and the third indicator scored 72%. Interviews with teachers revealed that although learning media such as PowerPoint and student worksheets were used, science literacy skills were not taught or assessed in detail. These findings highlight the importance of developing more innovative teaching methods and using technology, multimedia, and practical exercises to improve students' science literacy skills